1997
DOI: 10.1289/ehp.9710578
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of hexachlorobenzene in humans: association between serum levels and urinary metabolites in a highly exposed population.

Abstract: Serum and urine from 100 subjects of a general population highly exposed to airborne hexachlorobenzene (HCB) were analyzed to obtain new insights into the metabolism of this ubiquitous compound. HCB was detected in all serum samples with concentrations ranging between 1.1 and 953 ng/ml. The major known metabolites of HCB were investigated in urine collected over 24 hr. Pentachlorophenol (PCP) was detected in all urines with values ranging between 0.58 and 13.9 micrograms excreted in 24 hr [mean +/- standard de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(24 citation statements)
references
References 23 publications
4
19
0
1
Order By: Relevance
“…10 Negative ion chemical ionization gas chromatography coupled to mass spectrometry was used to confirm the presence of these compounds in the samples.…”
Section: Analysis Of Organochlorine Compounds In Serummentioning
confidence: 99%
“…10 Negative ion chemical ionization gas chromatography coupled to mass spectrometry was used to confirm the presence of these compounds in the samples.…”
Section: Analysis Of Organochlorine Compounds In Serummentioning
confidence: 99%
“…The porphyrin profile of the highly exposed subjects was normal (17). Analysis of HCB metabolism and excretion in urine and feces revealed a strong correlation between HCB serum concentrations and pentachlorobenzenetiol (PCBT) in urine (18) and unmetabolized HCB (19).…”
mentioning
confidence: 99%
“…Furthermore, beta-HCH was detected at trace levels in blood sera when its levels in milk fell below the analytical limits. As pointed out by other authors (Gupta et al, 1978, To-Figueras et al, 1997, Waliszewski et al, 2004, the results of the study reported by Ronchi and Danieli (2008) suggest a high sensibility of blood as an early indicator of OCP exposure, thus making cattle blood sampling an useful technique in biomonitoring plans to prevent animal exposure to agro-environmental pollution. The pollution by polychlorodibenzodioxins and -furans (PCDDs and PCDFs) and dioxin-like polychlorobiphenyls (DL-PCBs) of food of animal origin can give an useful indication in determining the link between livestock and the territory contamination, especially for extensive and outdoor farming systems.…”
Section: Persistent Organic Pollutants and Livestock Production Systemsmentioning
confidence: 76%